ANALISIS pH, TDS, TOTAL HARDNESS, ALKALINITY, DAN SILICA PADA BOILER FEET WATER DI PT. SOCFINDO PERKEBUNAN KELAPA SAWIT DI SEUNAGAN - Maulizar, Alvi; Masykur, Masykur; Supardi, Joli (universitas teuku umar, 2022)
The basic need of living things that is very important and cannot be separated is water. Various industrial activities require water for processing activities such as the palm oil industry, the palm oil industry is required to use water with good conditions such as proper chemical treatment. The power plant at PT. Socfindo Seunagan, requires water for steam needs from the boiler. Boiler is a closed place to produce steam from heating water. The boiler system, among others, consists of 3 parts, namely the water line system and steam system, fuel system and boiler system. Part of the steam system requires a lot of water to be adjusted automatically so that the steam in the system is met. The boiler feed water used must be able to meet the requirements as a source of steam and can prevent the formation of corrosion in the pipes. Therefore researchers are trying to maintain the stability of boiler feed water by maintaining pH, therefore it is necessary to analyze pH, TDS, Total hardness, Alkalinity, and SILICA in boiler feed water.